THE QUR’ANIC JESUS - Waryono Abdul Ghafur; Zaenuddin Hudi Prasojo; Mohammed Sahrin Bin Haji Masri (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2019)
This article examines the theological polemics between Islam and Christianity focusing on the prophetic attribution of Isa al-Masih in Islamic tradition. It takes a close look at the Qur’anic construction upon the Prophet Isa al-Masih as a human being who served as a messenger of God, while briefly comparing the Islamic construction to the Christian tradition projecting Isa-al-Masih as the son of God. Rather than emphasising differences between the two traditions, this article, through the Quranic concept kalimatun sawa’ (the shared principle or meeting point), sheds a new light on a shared belief between Islam and Christian traditions. Both Islam and Christianity believe that Isa al-Masih is the saviour for humanity, the liberator for the weak and the oppressed. The Qur’an maintains Isa al-Masih as one of the ulul azmi meaning that the prophets who successfully liberated his people.